Online Dispute Resolution in the Context of the African Continental Free Trade Agreement Protocol on Digital Trade - Cupido, Robin (Comparative and International Law Journal of Southern Africa, 2025)
The African Continental Free Trade Agreement was adopted in 2018 to establish the African Continental Free Trade Area. It introduced various provisions aimed at supporting the various aspects of such establishment, including the promotion of an intra-African digital economy. The latter goal was achieved through the adoption of the Protocol to the Agreement Establishing the African Continental Free Trade Area on Digital Trade (DTP) in 2024. The purpose of the DTP is to support and enable digital trade in Africa, promoting sustainable socio-economic development and the eventual digital transformation of the continent. One of the ways in which digital trade in Africa is to be supported is through the establishment of a regulatory framework to govern all aspects of digital trade, from pre-contractual negotiations to the resolution of disputes arising from such trade. In respect of the latter, it is suggested that there is room for a dispute resolution system outside of traditional litigation, one that is specifically suited to the online environment. Online Dispute Resolution is suggested as a system that is flexible and cost-effective enough to resolve cross-border online trades without the need to traverse jurisdictional rules and foreign legal systems. This work contains an examination of the DTP and a consideration of whether ODR could find application in Africa, subject to its provisions. The leading African countries in information and communications technology are also assessed to see whether the continent is ready to introduce ODR as a means of supporting the aims of the DTP.